AIDS hits home - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Everyone knew it would happen. AIDS is now accepted as a major cause of the slump experienced in small farmer production in Zimbabwe ? and many other countries. Most families have lost one or both parents, according to the Zimbabwean Farmer journal....